AB0048 Development of The New Rheumatoid Arthritis Disease Activity Marker Using Glycosylation Change of MMP-3. (15th July 2016) - Takeshita, M.; Suzuki, K.; Takeuchi, T.
Abstract : Background: It is known that almost all secreted proteins are glycosylated, that glycosylation patterns are influenced by cellular differentiation, and that serum glycoproteins exhibiting disease-associated glycosylation changes have potential to be biomarkers [1]. In rheumatoid arthritis (RA), C-reactive protein (CRP) and matrix metalloproteinase-3 (MMP-3) are widely used as serologic disease activity markers, but they lack sufficient specificity or precision. Thus, development of a RA-specific fine disease activity marker is needed. Objectives: We focused on an existing marker, MMP-3, and examined the association between its glycosylation pattern and RA disease activity. Methods: Serum was taken from RA patients (n=24) whose disease activity was scored using composite measures, and MMP-3 immunoprecipitated and subjected to recently developed antibody-overlay lectin microarray analysis. A disease activity index was developed based on lectin signal, and validated using another cohort, which included 60 serum samples from 30 RA patients, before and after treatment. Synovial fluid MMP-3 in RA and osteoarthritis (OA) patients was also analysed. Results: Intense signals were observed on the O-glycan binding lectins (ABA, ACA, and Jacalin) and a sialic acid binding lectin (ACG) by applying sub-nanogram levels of serum MMP-3. Jacalin and ABA, ACA, and ACG revealed differences in MMP-3 quality and quantity, respectively. The resultant index, ACG/Jacalin, correlated with disease activity. This correlation was validated using second cohort (r 2 =0.341, p <0.0001), and the correlation was greater than those of MMP-3 and CRP. In addition, the change in ACG/Jacalin and disease activity before and after treatment also correlated. Furthermore, we confirmed that MMP-3, which generated a high ACG/Jacalin score, accumulated in RA but not OA patient synovial fluid. Conclusions: We succeeded in development a new RA specific and sensitive disease activity marker using glycosylation change of MMP-3. The difference in quality but not quantity of MMP-3 may be a useful index for estimating RA disease activity. References: Kuno A, et al. Methods Mol Biol. 2014;1200:265–285. Acknowledgement: We especially thank Mr. Atsushi Kuno and Hisashi Narimatsu, the members of Research Center for Medical Glycoscience (RCMG), National Institute of Advanced Industrial Science and Technology (AIST) for their support and cooperation, and Ms. Harumi Kondo and Ms. Yuki Otomo for their assistance. Disclosure of Interest: M. Takeshita: None declared, K. Suzuki: None declared, T. Takeuchi Grant/research support from: AbbVie GK, Asahikasei Pharma Corp., Astellas Pharma, Astra Zeneca K.K., Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co. Ltd., Eisai Co. Ltd., Eli Lilly Japan K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co. Ltd., SymBio Pharmaceuticals Ltd., Takeda Pharmaceutical Co. Ltd., Teijin Pharma Ltd., Taisho Toyama Pharmaceutical Co. Ltd., and UCB Japan Co. Ltd., Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., Abbivie GK, Daiichi Sankyo Co. Ltd., Bristol–Myers K.K., Nipponkayaku Co. Ltd, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Eisai Co. Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Takeda Pharmaceutical Co. Ltd., Astellas Pharma, Diaichi Sankyo Co. Ltd., Celtrion, Nipponkayaku Co. Ltd